Rapid Extragranular Plasticity in the Absence of Thalamocortical Plasticity in the Developing Primary Visual Cortex - Trachtenberg, Joshua T. (2000)
Monocular deprivation during early postnatal development remodels the circuitry of the primary visual cortex so that most neurons respond poorly to stimuli presented to the deprived eye. This rapid physiological change is ultimately accompanied by a matching anatomical loss of input from the deprived eye. This remodeling is thought to be initiated at the thalamocortical synapse. Ocular dominance plasticity after brief (24 hours) monocular deprivation was analyzed by intrinsic signal optical imaging and by targeted extracellular unit recordings. Deprived-eye responsiveness was lost in the extragranular layers, whereas normal binocularity in layer IV was preserved. This finding supports the hypothesis that thalamocortical organization is guided by earlier changes at higher stages.